Investigating ADHD Symptoms and Sleep Disturbances in Young Adults: A Cross-Sectional Study - Demirkan AK; Semiz UB (Nature and Science of Sleep)
Arda Kazim Demirkan,1,2 Umit Basar Semiz3 1Department of Psychiatry, Samsun LIV Hospital, Samsun, Turkey; 2Department of Psychiatry, Agri Training and Research Hospital, Agri, Turkey; 3Faculty of Political Science, Ankara Medipol University, Ankara, TurkeyCorrespondence: Arda Kazim Demirkan, Samsun LIV Hospital, Hancerli, Fatih Sultan Mehmet Cd, No: 155, 55020, Ilkadim, Samsun, Turkey, Tel +90 546 219 30 99, Fax +90 362 999 80 00, Email ardakazimdemirkan@gmail.comPurpose: Attention-deficit/hyperactivity disorder (ADHD), a prevalent condition affecting 2.5– 5% of adults, impacting daily functioning. Sleep quality is essential for cognitive and socio-emotional well-being, and the association between ADHD symptoms and sleep disturbances necessitates identifying populations at risk. This study aimed to assess the associations between ADHD symptoms and sleep disorders by conducting a thorough assessment of sleep measures in a cross-sectional group of university students.Patients and Methods: Recruiting participants from a Turkish university (n=503; mean age=21.3 ± 1.8 years), subgroups were formed based on ADHD scores from the Adult ADHD Self-report Scale. Sleep was assessed using the Van Dream Anxiety Scale, Pittsburgh Sleep Quality Index (PSQI), and Epworth Sleepiness Scale (ESS). Beck Depression Inventory (BDI) was employed to evaluate depressive symptoms.Results: ADHD symptoms group exhibited higher dream-related anxiety, PSQI, ESS, and BDI scores. Nightmares were more prevalent in the ADHD symptoms group. Subjective sleep measures showed differences in various domains, emphasizing poorer sleep quality in the ADHD symptoms group. Correlation analyses revealed intricate relationships between socio-economic factors, psychiatric health, family history, ADHD symptoms, nightmares, and sleep aspects.Conclusion: University students with ADHD symptoms face increased susceptibility to insufficient sleep, impacting daytime functioning and academic performance. Findings underscore the need for increased attention to sleep health in this population.Plain Language Summary: We wanted to understand how sleep problems affect university students who have symptoms of attention-deficit/hyperactivity disorder (ADHD). ADHD can make it harder to focus, stay organized, and manage time. People with ADHD often report having trouble sleeping, but we wanted to learn more about how sleep and mood might be linked to these symptoms. To do this, we asked students to fill out questionnaires about their sleep habits, feelings, and ADHD symptoms. We compared students with ADHD symptoms to those without.We found that students with ADHD symptoms: (1) Had more trouble falling or staying asleep, (2) Felt sleepier during the day, (3) Had more nightmares, (4) Reported feeling more depressed. We also discovered that poor sleep and low mood were strongly related to ADHD symptoms. In fact, sleep and mood explained about 68% of the differences in ADHD symptom levels.Students with ADHD symptoms were also more likely to sleep fewer hours than recommended. This can affect learning, memory, and daily life. Things like staying up late to study, using phones or computers at night, or having a busy social life may make sleep worse.Even though the study relied on self-reported answers and included students from only one university, the results suggest that better sleep and emotional support might help reduce ADHD symptoms and improve students’ well-being.Our research highlights the importance of supporting healthy sleep habits and mental health in students who experience attention difficulties.Keywords: ADHD, sleep disturbances, young adults, university students, sleep quality